AODTU-008 Can transient elastrography predict development of portal hypertension and or hepatic decompensation in individuals with cirrhosis?. (17th June 2017) - Hashim, A; Haddadin, Y; Macken, L; Bremner, S; Keller, M; File, A; Gilleece, Y; Tibble, J; Verma, S
Abstract : Introduction: Liver stiffness measurement (LSM) using Transient Elastography (TE) is a powerful non-invasive tool for staging hepatic fibrosis. Our aim was to establish the ability of LSM in predict ing liver-related complications and mortality. Method: We retrospectively reviewed consecutive patients who underwent outpatient TE between April 2013 & April 2014 (with follow up until April 2016) at a teaching hospital in SE England. Cox regression analysis was applied to determine the relationship between LSM and liver-related events or mortality. Liver-related events were defined as one or more of the following: development of portal hypertension, hepatic decompensation, hepatocellular cancer and or need for transplantation. Results: A total of 403 patients fulfilled study criteria of whom 155 (38.5%) had LSM > 8 kPa indicating clinically significant hepatic fibrosis. Overall 94 (23%) had cirrhosis (LSM > 13 kPa). The mean age of the cohort was 50±13.4 years and 271 (67%) being males. Indication for performing TE was viral hepatitis (n=225, 56%) followed by alcohol (47, 12%) and non-alcoholic fatty liver disease (n=41, 10%). Of those with cirrhosis (n=94), the mean age of this subgroup was 56±10 years and 68 (72%) were males and median LSM was 22.1 kPa (13.1–75 kPa). Of those who had bloods results available at baseline (88/94), the majority had Child-Pugh score (CPS) A (n=73, 83%) while all of the remaining were in CPS B (n=15, 17%). The mean MELD score was 9.8±4.6. Almost half of the patients (n=44/94, 47%) with cirrhosis developed one or more liver-related complications. The majority (n=40/94) had the complications at baseline (i.e within 6 months following index LSM.). The median LSM score at baseline for those with liver-related complications was significantly higher than that of the patients without these events (35.3 vs 20.9 kPa, p=0.003). Moreover, of the 55 patients who underwent gastroscopy, those with oesophageal varices at baseline (20, 36.3%) had significantly higher median LSM than those without varices (48 vs 21.5 kPa, p=0.0003). Age, gender, aetiology of liver disease and presence of comorbidities did not independently influence the development of varices or liver-related events. Twelve patients (13%) with cirrhosis (n=94) died within a median time to death of 8 months (1–24 months). The median stiffness score of those who died was not different from that of the surviving group (24.3 vs 21.7 kPa). Conclusion: This retrospective cohort study suggests that TE could potentially be a useful non-invasive tool in predicting portal hypertension and or development of hepatic decompensation in individuals with cirrhosis. Disclosure of Interest: None Declared